The effect of left atrial remodeling after cryoballoon ablation and radiofrequency ablation for paroxysmal atrial fibrillation. Issue 1 (18th November 2020) - Wang, Xule; Song, Beibei; Qiu, Chunguang; Han, Zhanying; Wang, Xi; Lu, Wenjie; Chen, Xiaojie; Chen, Yingwei; Pan, Liang; Sun, Guoju; Qin, Xiaofei; Li, Ran
Abstract: Background: Cryoballoon ablation (CBA) and radiofrequency ablation (RFA) are the most common procedures used to treat refractory atrial fibrillation (AF) and are performed through pulmonary vein isolation (PVI). Studies have shown that CBA can approximately match the therapeutic effects of RFA against AF. However, few studies have investigated the difference between CBA and RFA of the effects on left atrial remodeling for paroxysmal AF. Objective: Atrial remodeling is considered pivotal to the occurrence and development of AF, therefore we sought to assess the influence of atrial remodeling in patients with paroxysmal AF after CBA and RFA in this study. Methods: In this nonrandomized retrospective observational study, we enrolled 328 consecutive patients who underwent CBA or RFA for refractory paroxysmal AF in May 2014 to May 2017 in our hospital. After propensity score matching, 96 patients were included in the CBA group, and 96 were included in the RFA group. Patients were asked to undergo a 12‐lead electrocardiogram, a 24‐h Holter monitor, and an echocardiogram and to provide their clinical history and symptoms at 6 months and 1, 2, and 3 years postprocedurally. Electrical remodeling of the left atrium was assessed by P wave dispersion (Pdis); structural remodeling was assessed by the left atrium diameter (LAD) and left atrial volume index (LAVI) during scheduled visits. Results: As of January 2020, compared with baseline, at 1 year, 2 years, and 3 years after ablation, the average changes in Pdis (∆Pdis), LAD (∆LAD), and LAVI (∆LAVI) were significant in both the CBA and RFA groups. Six months after ablation, ∆Pdis, ∆LAD, and ∆LAVI were greater in the CBA group than in the RFA group. There was no significant difference between the two groups in AF/flutter recurrence, but the AF/flutter‐free survival time of CBA group may be longer than RFA group after 2 years after ablation. A higher ∆Pdis, ∆LAD, or ∆LAVI at 1 year after ablation may increase AF/flutter‐free survival. Conclusions: Although CBA and RFA are both effective in left atrial electrical and structural reverse‐remodeling in paroxysmal AF, CBA may outperform RFA for both purposes 6 months after ablation. However, during long‐term follow‐up, there was no significant intergroup difference.